Wapnowanie jako metoda immobilizacji metali ciężkich w glebach = Liming as a method of heavy metals immobilization in soils - Przewocka, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this thesis issues related to the causes and effects of soils acidification in an agricultural environment of Huta Miedzi GŁOGÓW were discussed, also assessment of the risk analysis based on the bioavailability of heavy metals in various pH conditions was carried out. Studies have shown that acidification of soils lacated in the nearest vicinity of the plant is considered to be one of the main factors contributing to the increase of heavy metals mobility.
Keywords: wapnowanie gleb; rekultywacja; metale ciężkie; Huta Miedzi "Głogów"; soils liming; soils remediation; heavy metals; Copper Smelter Głogów